Characterization of mortality rates resulting from traffic accidents involving cycles - Angela Normayda Jorge Miguez; Haray Godoy del Sol; Mavis Ortis Sagasta (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Background: Traffic accidents are a highly complex phenomenon due to the variety of factors involved in their occurrence. They have become more relevant as the fight against illnesses becomes more effective. Objective: To characterize the mortality rates resulting from traffic accidents involving cycles. Methods: Descriptive study on case series conducted at the General University Hospital "Dr. Gustavo Lima Aldereguía " in Cienfuegos on all deaths related to traffic accidents involving cycles from January 1st to December 31st , 2009. Variables that were analyzed: age, sex, time of the accident, predominantly affected anatomical region, direct cause of death and ingestion of alcohol. Results: There were 26 deaths (6.4 per 100 000 inhabitants), mainly in the group from 15 to 29 years old, predominantly males with 23 cases (88.4%).53, 8% of them were workers and 23% were students. There was a predominance of fatalities in the hours between 6:00 pm and 11:59 pm. The most affected anatomic region was the head (61.5%), 46, 2 % of deaths had more than 50 mg of alcohol in blood and the predominant direct cause of death was the injuries of higher nervous centers. Conclusions: Traffic accidents involving cycles are more frequent in young males . They are related to the ingestion of alcohol and usually affect the head region.